NOVEL APPROACHES TO MODELING AND CALCULATING FLOWS PARAMETERS OF DENSE POLYDISPERSED SUSPENSIONS - Kazenova Aykerim,; Brener Arnold,; Golubev Vladimir Grigorievich,; Leudanski Aliaksandr Eduardovich,; Kenzhalieva Gulmira,; Shapalov Shermakhan Kuttibayevich,; Zhumadullayev Daulet Koshkarovich, (Academic Journal of Physical and Chemical Sciences, 2019)
Modeling the sediments of dense polydisperse suspensions and the calculation of the corresponding equipment have some features that are often not taken into account in engineering calculations. This article provides an overview and analysis of these features, and also outlines ways to solve the problems arising in the calculation of the deposition of polydisperse suspensions in relation to specific structures of industrial apparatuses. New approaches to the mathematical description of the flow of dense suspensions and sediments taking into account the experimentally observed characteristics of the flow of such systems have been offered. The modern model that allows describing this phenomenon and eliminating the corresponding limitations of known models has been submitted. The submitted model describes the fluidity of the medium in a wide range of the content of dispersed solid phase even at its high concentrations. Such result has been achieved thanks to a new heuristic expression for calculating the relative viscosity of the suspension as a function of the concentration of the solid phase. The formula for calculating the outflow rate from buffer tanks with accounting to the energy dissipation has been submitted. Such an approach allows to propose a calculation scheme that can be adapted to different rheological models.